Metabolic reprogramming of terminally exhausted CD8+ T cells by IL-10 enhances anti-tumor immunity - Yugang Guo (2022)
T cell exhaustion presents one of the major hurdles to cancer immunotherapy. Among exhausted CD8+ tumor-infiltrating lymphocytes, the terminally exhausted subset contributes directly to tumor cell killing owing to its cytotoxic effector function. However, this subset does not respond to immune checkpoint blockades and is difficult to be reinvigorated with restored proliferative capacity. Here, we show that a half-life-extended interleukin-10–Fc fusion protein directly and potently enhanced expansion and effector function of terminally exhausted CD8+ tumor-infiltrating lymphocytes by promoting oxidative phosphorylation, a process that was independent of the progenitor exhausted T cells. Interleukin-10–Fc was a safe and highly efficient metabolic intervention that synergized with adoptive T cell transfer immunotherapy, leading to eradication of established solid tumors and durable cures in the majority of treated mice. These findings show that metabolic reprogramming by upregulating mitochondrial pyruvate carrier-dependent oxidative phosphorylation can revitalize terminally exhausted T cells and enhance the response to cancer immunotherapy.